The role of β-hydroxybutyrate testing in ketogenic metabolic therapies - Fante, Cristina; Spritzler, Franziska; Calabrese, Lori; Laurent, Nicole; Roberts, Caroline; Deloudi, Sofia (Frontiers in Nutrition, 2025)
Accurate assessment of dietary adherence and metabolic outcomes remains a critical challenge in most nutrition studies. Ketogenic metabolic therapies (KMTs) provide a unique advantage by inducing nutritional ketosis and enabling the use of ketone bodies as biomarkers of metabolic state. This narrative review investigates the role of ketone testing as an integral component of KMTs. We introduce the key biomarkers and testing modalities currently used and present a comprehensive overview of the use of capillary blood β-hydroxybutyrate (BHB) testing across diverse therapeutic areas. Capillary blood BHB testing plays a multifaceted role in KMTs: it enables objective monitoring of dietary adherence, supports the interpretation of clinical outcomes, and informs personalized treatment adjustments based on individual metabolic responses. Additionally, it may facilitate behavior change through real-time feedback. Broader implementation of ketone testing in both clinical and research settings will require thoughtful protocol design that accounts for individual preferences and tolerability, continued technological innovation to enhance user experience, and further research into the relationship between ketone levels and therapeutic outcomes.